2008
DOI: 10.3844/ajessp.2008.164.172
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Stormwater Runoff and Landfill Leachates Using a Surface Flow Constructed Wetland

Abstract: A surface flow wetland was constructed in the Burnside Industrial Park, Dartmouth, Nova Scotia, to treat stormwater runoff from the surrounding watersheds which are comprised primarily of commercial properties and two former landfills. The aim was to protect a freshwater ecosystem that consists of a 4.6 km long brook and two lakes. The ability of the constructed wetland to retain iron and manganese from the influent water was investigated and the change in pH of the water as it flowed through the cells was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The average pH value for 12.1 mmol·L −1 urea was similar to the finding that pH ranged from 7 to 7.6 in the horizontal flow reed beds, and Snow et al . found that, in 2004 and 2006, the pH of the water in the CWs had average inlet values of 6.7 and 6.3, and average outlet values of 7.3 and 6.7, respectively . It was reported that higher pH enhanced CH 4 production and lower pH inhibited CH 4 production through the direct inhibition of methanogens and indirectly through its effects on fermentation .…”
Section: Resultsmentioning
confidence: 99%
“…The average pH value for 12.1 mmol·L −1 urea was similar to the finding that pH ranged from 7 to 7.6 in the horizontal flow reed beds, and Snow et al . found that, in 2004 and 2006, the pH of the water in the CWs had average inlet values of 6.7 and 6.3, and average outlet values of 7.3 and 6.7, respectively . It was reported that higher pH enhanced CH 4 production and lower pH inhibited CH 4 production through the direct inhibition of methanogens and indirectly through its effects on fermentation .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the SEM images, the size of the particles increased with the increasing water content. The precipitation of MnCO 3 occurs with the reaction of H 2 O and CO 2 , as shown in the following equations [22].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, much attention has been directed to FWS-CTWs to treat wastewater and enable sustainable resource management or ecosystem restoration (Ghermandi et al 2007;Harrington et al 2007;Scholz et al 2007;Vymazal 2007;Rousseau et al 2008;Snow et al 2008;Kadlec 2009;Li et al 2009). FWS-CTWs have been applied at different stages of treatment of wastewater from different sources with varying pollution characteristics and are suitable in all climates (Kadlec and Wallace 2009).…”
Section: Applications Of Fws-ctwsmentioning
confidence: 99%
“…Constructed treatment wetlands (CTWs) are used to remove a wide range of pollutants such as organic compounds, suspended solids, pathogens, metals, and excess nutrients (e.g., N and P) from various wastewaters including stormwater runoff and municipal wastewater (Ghermandi et al 2007;Vymazal 2007;Snow et al 2008;Cooper 2009;Kadlec 2009). Because of high removal efficiency, low cost, water and nutrient reuse, and other ancillary benefits, CTWs have become a popular option for wastewater treatment (Ghermandi et al 2007;Rousseau et al 2008;Llorens et al 2009;Kadlec 2009).…”
Section: Introductionmentioning
confidence: 99%